Monitoring disulfide bond formation in the eukaryotic cytosol - Østergaard, Henrik (The Rockefeller University Press, 2004)
Glutathione is the most abundant low molecular weight thiol in the eukaryotic cytosol. The compartment-specific ratio and absolute concentrations of reduced and oxidized glutathione (GSH and GSSG, respectively) are, however, not easily determined. Here, we present a glutathione-specific green fluorescent protein–based redox probe termed redox sensitive YFP (rxYFP). Using yeast with genetically manipulated GSSG levels, we find that rxYFP equilibrates with the cytosolic glutathione redox buffer. Furthermore, in vivo and in vitro data show the equilibration to be catalyzed by glutaredoxins and that conditions of high intracellular GSSG confer to these a new role as dithiol oxidases. For the first time a genetically encoded probe is used to determine the redox potential specifically of cytosolic glutathione. We find it to be −289 mV, indicating that the glutathione redox status is highly reducing and corresponds to a cytosolic GSSG level in the low micromolar range. Even under these conditions a significant fraction of rxYFP is oxidized.